Long-term evolution of winter habitats in Poyang Lake derived from satellite imagery using machine learning methods - Siqin Qi; Jiayi Pan; Adam T. Devlin (Frontiers of Earth Science, 2025)

Reply to “timing errors in global sea level observations” (Pan et al., 2025) - Philip R. Thompson; Ayesha S. Genz; Matthew J. Widlansky; Gary T. Mitchum; Elizabeth Bradshaw; Adam T. Devlin; Begoña P. Gómez; Ivan D. Haigh; Marta Marcos; Andrew Matthews; Mark A. Merrifield (Ocean Dynamics, 2025)

Editorial: Advances in ecological environment changes in coastal and estuarine waters in response to hydrodynamic variability - Jiayi Pan; Yeqiang Shu; Zhe-Wen Zheng; Adam T. Devlin; Majid Nazeer; Andrew M. Fischer (Frontiers in Marine Science, 2024)

Global water level variability observed after the Hunga Tonga-Hunga Ha'apai volcanic tsunami of 2022 - Adam T. Devlin; David A. Jay; Stefan A. Talke; Jiayi Pan (Ocean Science, 2023)
The eruption of the Hunga Tonga-Hunga Ha'apai volcano on 15 January 2022 provided a rare opportunity to understand global tsunami impacts of explosive volcanism and to evaluate future hazards, including dangers from “volcanic meteotsunamis” (VMTs) induced by the atmospheric shock waves that followed the eruption. The propagation of the volcanic and marine tsunamis was analyzed using globally distributed 1 min measurements of air pressure and water level (WL) (from both tide gauges and deep-water buoys). The marine tsunami propagated primarily throughout the Pacific, reaching nearly 2 m at some locations, though most Pacific locations recorded maximums lower than 1 m. However, the VMT resulting from the atmospheric shock wave arrived before the marine tsunami and propagated globally, producing water level perturbations in the Indian Ocean, the Mediterranean, and the Caribbean. The resulting water level response of many Pacific Rim gauges was amplified, likely related to wave interaction with bathymetry. The meteotsunami repeatedly boosted tsunami wave energy as it circled the planet several times. In some locations, the VMT was amplified by as much as 35-fold relative to the inverse barometer due to near-Proudman resonance and topographic effects. Thus, a meteotsunami from a larger eruption (such as the Krakatoa eruption of 1883) could yield atmospheric pressure changes of 10 to 30 mb, yielding a 3–10 m near-field tsunami that would occur in advance of (usually) larger marine tsunami waves, posing additional hazards to local populations. Present tsunami warning systems do not consider this threat.

Influence of the upper mixed layer depth on Langmuir turbulence characteristics - Guojing Li; Changming Dong; Jiayi Pan; Adam T. Devlin; Dongxiao Wang (Journal of Oceanology and Limnology, 2023)

Tidal variability in the Hong Kong region - Adam T. Devlin; Jiayi Pan; Hui Lin (Ocean Science, 2019)
Mean sea level (MSL) is rising worldwide, and correlated changes in ocean tides are also occurring. This combination may influence future extreme sea levels, possibly increasing coastal inundation and nuisance flooding events in sensitive regions. Analyses of a set of tide gauges in Hong Kong reveal complex tidal behavior. Most prominent in the results are strong correlations of MSL variability to tidal variability over the 31-year period of 1986–2016; these tidal anomaly correlations (TACs) express the sensitivity of tidal amplitudes and phases (M2, S2, K1, O1) to MSL fluctuations and are widely observed across the Hong Kong region. At a few important harbor locations, time series of approximations of the parameter δ-HAT, computed from combinations of the major tidal constituents, are found to be highly sensitive to MSL variability, which may further increase local flood levels under future MSL rise. Other open-water locations in Hong Kong only show TACs for some individual tidal constituents but not for combined tidal amplitudes, suggesting that the dynamics in enclosed harbor areas may be partially frequency dependent and related to resonance or frictional changes. We also observe positive correlations of the fluctuations of diurnal (D1) tides to semidiurnal (D2) tides at most locations in the region, which may lead to further amplified tidal ranges under MSL. It is demonstrated here that tidal changes in the Hong Kong coastal waters may be important in combination with MSL rise in impacting future total water levels.

Remote sensing study of wetlands in the Pearl River Delta during 1995–2015 with the support vector machine method - Xiaosong Han; Jiayi Pan; Adam T. Devlin (Frontiers of Earth Science, 2018)

Can tidal perturbations associated with sea level variations in the western Pacific Ocean be used to understand future effects of tidal evolution? - Adam T. Devlin; David A. Jay; Stefan A. Talke; Edward Zaron (Ocean Dynamics, 2014)